The influence of land use change on soil erosion in the Genale catchment, southern Ethiopia - Bout, B. van den (Utrecht University, 2015)
Soil erosion forms one of the main causes of land degradation in third world countries. The subject of this research was the inuence of land use and land use change on soil erosion in the upper Genale catchment, Southern Ethiopia. A land use classification was implemented for Landsat satellite images from 1985, 1993, 2003 and 2015. Using a hydro- logical model of the catchment, created with the Soil and Water Assessment Tool (SWAT), an erosion model was developed. The results of an erosion survey, which focused on diferent land uses, were used for calibration and validation. Using a continuation of land use changes in the past decades, erosion predictions were made for 2025. Land use change within the area was substantial with an increase of farmland from 10 percent to 62 percent between 1985 and 2015. Forest and grassland cover decreased from 76 percent to 32 percent. Besides population growth as the main driver of land use change, financial opportunities and government policies have been observed to inuence land use dynamics in the region. During the erosion survey the average soil erosion was 3.9 t ha-1 during 5 weeks. An average annual erosion of 41 t ha-1 y-1 was predicted for 2015. Both the erosion survey and the model revealed agricultural land to be the biggest inuence on soil erosion. Especially annual crops which exhibited soil erosion up to 10 times as high as other farms. The erosion was estimated to have increased by 189 percent between 1985 and 2015. When land use changes continue linearly, erosion will increase to 50 t ha-1 y-1 in 2025. Soil and water conserving measures in combination with irrigation projects are needed but should be strategically chosen. Good decision making is necessary to maintain agricultural potential in the area.